Strategi Guru dalam Meningkatkan Minat dan Motivasi Belajar Siswa: Perspektif Guru dan Siswa dalam Menghafal Al-Qur’an - Fatimah Azzahra; Kania Salma Alfiana; Maheswari Chandra Kirana Putri; Nurul Ibni Sabella (STAI AL-AMIN, 2025)
This study aims to analyze the teacher's strategy in increasing interest and motivation to memorize the Qur'an in class 2A students of SDI Sahabat Ilmu, Karawang. The focus of this research includes factors that influence student interest and motivation, obstacles faced by teachers, and strategies applied. This research uses the Classroom Action Research method with the Kemmis and McTaggart model which contains the planning stage, action stage, observation stage, and reflection stage. The subjects of this study were students of class 2A SDI Sahabat Ilmu Karawang, totaling 28 students. The results showed that internal factors such as self-motivation, understanding the context of the verse, and good learning habits, and external factors such as family support, educational environment, and the influence of friends play an important role in increasing student interest and motivation. The main obstacles faced by teachers are the lack of parental involvement in the memorization process at home and limited time at school. The strategies applied by teachers include the Ali and Shafi'I methods, providing motivation and praise, and using books as learning media. This strategy has proven effective in increasing students' enthusiasm and interest in memorizing the Qur'an although it requires continuous efforts to overcome existing obstacles.